On the clouds: a new way of computing. - Han Y (Information Technology & Libraries, 2010)
This article introduces cloud computing and discusses the author's experience 'on the clouds.' The author reviews cloud computing services and providers, then presents his experience of running multiple systems (e.g., integrated library systems, content management systems, and repository software). He evaluates costs, discusses advantages, and addresses some issues about cloud computing. Cloud computing fundamentally changes the ways institutions and companies manage their computing needs. Libraries can take advantage of cloud computing to start an IT project with low cost, to manage computing resources cost-effectively, and to explore new computing possibilities.